An Optimization Approach for Load Balancing in Parallel Link Discovery - Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (SEMANTiCS 2015)
Many of the available RDF datasets describe millions of resources by using billions of triples. Consequently, millions of links can potentially exist among such datasets. While parallel implementations of link discovery approaches have been developed in the past, load balancing approaches for local implementations of link discovery algorithms have been paid little attention to. In this paper, we thus present a novel load balancing technique for link discovery on parallel hardware based on particle-swarm optimization. We combine this approach with the Orchid algorithm for geo-spatial linking and evaluate it on real and artificial datasets. Our evaluation suggests that while naïve approaches can be super-linear on small data sets, our deterministic particle swarm optimization outperforms both naïve and classical load balancing approaches such as greedy load balancing on large datasets.
Keywords: 2015 sys:relevantFor:geoknow geoknow ngonga sherif simba dice group_aksw sys:relevantFor:infai sys:relevantFor:bis SIMBA limes

Managing Geospatial Linked Data in the GeoKnow Project - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; Garcia-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Hoeffner, Konrad; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Stadler, Claus; Wauer, Matthias; et al. (The Semantic Web in Earth and Space Science. Current Status and Future Directions)
Keywords: 2015 group_aksw sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:geoknow lehmann ngonga MOLE sherif simba dice hoeffner geoknow wauer westphal

The GeoKnow Handbook - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; Buehmann, Lorenz; Garcia-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Hoeffner, Konrad; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Pietzsch, Rene; Isele, Robert; et al.
Keywords: 2015 group_aksw sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:geoknow lehmann ngonga MOLE sherif simba dice hoeffner geoknow westphal buehmann

Short-and medium-term effects of informal care provision on female caregivers’ health - Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)

Jeder zehnte Mensch war illegal - Schubert, Michael (Die neuen Deutschen. Vom Dreißigjährigen Krieg bis heute: 400 Jahre Einwanderung nach Deutschland)

Soziale Ausgrenzung und rassistische Verfolgung der Osnabrücker Sinti im Nationalsozialismus - Schubert, Michael; Cooper, Duncan (Topografien des Terrors. Nationalsozialismus in Osnabrück)

Einflüsse auf die Entwicklung der Bindungsorganisation von der frühen Kindheit in das Vorschulalter - Franke, Sebastian

Threatening customers not to return – An effective strategy for online retailers? - Feider, L.; Garnefeld, I.; Böhm, Eva (44th EMAC Annual Conference, Leuven)

Stock market reactions to customer service outsourcing in manufacturing firms - Eggert, A.; Böhm, Eva; Cramer, C. (2015 AMA Winter Academic Conference, San Antonio, TX)

Recognizing value creation opportunities in business markets - Böhm, Eva; Eggert, A.; Terho, H.; Ulaga, W.; Haas, A. (2015 AMA Winter Academic Conference, San Antonio, TX)

Stock market reactions to business service outsourcing in manufacturing firms - Eggert, A.; Böhm, Eva; Cramer, C. (44th EMAC Annual Conference, Leuven)

Constitutive Effects of Technological Frames in Everyday Interaction - Klowait, Nils (Sociology of Power)

Blickfinten im Basketball: Eine EEG-Studie - Koester, Dirk; Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Stressregulation und Sport. Tagungsband der 47. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Treffen ohne getroffen u werden: Fechter nutzen visuelle und akusti-sche Information zum Erkennen gegnerischer Angriffe - Allerdissen, M; Bläsing, Bettina; Güldenpenning, Iris; Schack, Thomas (Stressregulation und Sport. 47. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Der Einfluss strategischer Prozesse auf die Verarbeitung der Blickrichtung im Basketball: Eine EKP-Studie - Koester, Dirk; Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Abstracts of the 57th Conference of Experimental Psychologists (TeaP))

Schnell handeln ohne zu wissen warum? Die unbewusste Verarbeitung von Angriffstechniken im Kampfsport - Güldenpenning, Iris; Schack, Thomas (Stressregulation und Sport. Tagungsband der 47. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie)

Subliminal primes elicit independent motor responses - Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Abstracts of the 57th Conference of Experimental Psychologists (TeaP))

Visuomotor priming of power and precision grips - Güldenpenning, Iris; Seegelke, Christian; Schack, Thomas (57th Concference of Experimental Psychologists (TeaP))

Neurokognition der Blicktäuschung: Eine Studie im Basketball - Koester, Dirk; Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Moving Minds - Crossing Boundaries in Sport Science. Abstractband zum 22. dvs-Hochschultag)

Prokrastination: Problem oder Strategie? - Klingsieck, Katrin B. (Eile mit Weile. Aspekte der Be- und Entschleunigung in Wissenschaft und Kunst)

Procrastination - Klingsieck, Katrin B.; Steel, Piers (International Encyclopedia of Social & Behavioral Science)

CFD-Untersuchung der Fluiddynamik und des Wärmeübergangs bei einphasiger Strömung im welligen Spalt zwischen Thermoblechen - Piper, Mark; Tran, Julian M.; Kenig, Eugeny Y. (Chemie Ingenieur Technik)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Masked priming of complex movements: perceptual and motor processes in unconscious action perception - Güldenpenning, Iris; Braun, Jelena F; Machlitt, Daniel; Schack, Thomas (Psychological Research)

Neurophysiologische Korrelate der Verarbeitung der Blickrichtung im Basketball bei der Passbeurteilung - Koester, Dirk; Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (The Athlete’s Brain: Neuronale Aspekte motorischer Kontrolle im Sport. 14. Jahrestagung der dvs-Sektion Sportmotorik)

Minimum participation rules in international environmental agreements: empirical evidence from a survey among delegates in international climate negotiations - Kesternich, Martin (Applied Economics)
Keywords: Economics and Econometrics

Extreme weather experiences and climate change beliefs in China: An econometric analysis - Dai, Jing; Kesternich, Martin; Löschel, Andreas; Ziegler, Andreas (Ecological Economics)
Keywords: Economics and Econometrics; General Environmental Science

Entwurf und Anwendung einer erweiterten Zustandsüberwachung zur Verlässlichkeitssteigerung selbstoptimierender Systeme - Sondermann-Woelke, Christoph
Das Wirkparadigma der Selbstoptimierung ermöglicht mechatronischen Systemen sich autonom und flexibel an veränderte Betriebssituationen anpassen zu können. Um selbstoptimierende Systeme verlässlich zu gestalten und darüber hinaus Selbstoptimierung zur Verlässlichkeitssteigerung des Systems zu nutzen, werden in dieser Arbeit der Entwurf und die Anwendung einer erweiterten Zustandsüberwachung dargestellt. Darin wird eine klassische Zustandsüberwachung mit dem Wirkparadigma der Selbstoptimierung verbunden. Für den Entwurf der erweiterten Zustandsüberwachung wird aufgezeigt, welche Schritte erforderlich sind, damit das Wirkparadigma der Selbstoptimierung genutzt und gleichzeitig das selbstoptimierende System abgesichert werden kann. Die Basis für den Entwurf der erweiterten Zustandsüberwachung stellt die Spezifikation der Prinziplösung selbstoptimierender Systeme dar. So können das System und die erweiterte Zustandsüberwachung in den frühen Phasen des Entwicklungsprozesses konsistent entworfen werden. Hinsichtlich der Anwendung werden drei Aspekte betrachtet. Erstens werden die Entwurfsschritte anhand des Anwendungsbeispiels umgesetzt und bewertet. Zweitens werden die unterschiedlichen Betriebsstrategien auf einem realen Demonstrator implementiert und erprobt, um vor allem das Konzept des Umschaltens auf verlässlichkeitsorientierte Ziele im Fehlerfall zu bewerten. Drittens werden Simulationen durchgeführt, die über die Möglichkeiten des realen Demonstrators hinausgehen. Die exemplarische Anwendung zeigt, dass die erweiterte Zustandsüberwachung eine Steigerung der Verlässlichkeit im Betrieb mittels Selbstoptimierung ermöglicht.
Keywords: Verl{\

,,…, als habe dort niemals eine Insel gestanden.“ Wolfgang Hildesheimers und Hans Werner Henzes Das Ende einer Welt als Erzählung und Rundfunkoper - Eickmeyer, Jost; Tumat, Antje (Literatur für Leser)
An den Schluss seiner ersten unter dem programmatisch-spöttischen Titel Lieblose Legenden veröffentlichten Prosa-Sammlung setzt Wolfgang Hildesheimer effektvoll Das Ende einer Welt. Dem eschatologischen Beiklang der Rede vom Ende wird schon im Titel lakonisch Paroli geboten: Es handelt sich nur um das Ende ,,einer“ Welt, jedoch einer, die in aller hyperbolischen Absurdität mit europäischer Kunst und Kultur assoziiert werden kann, deren gewaltsamer Untergang in Diktatur und Krieg den Lesern sowohl 1952 als auch nach der letzten revidierten Publikation 1962 noch deutlich vor Augen gestanden haben dürfte. Das ,,Echte und Bleibende“, das die Marchesa di Montetristo (eine schon namentlich gekennzeichnete melancholische Version von Alexandre Dumas’ rachedurstigem Grafen) auf ihrer künstlichen Insel südöstlich von Murano pflegt, lässt sich als Sammelsurium alteuropäischer Kulturbeflissenheit lesen: an Personen ein Abraham-a-Santa-Clara-Forscher und ein Neo-Mystiker gleichen Namens, eine polnische Tänzerin, die als ,,Doppelbegabung“ (EW, 9) zugleich den Jugendstil erneuert, eine italienische Astrologin, die Kulturgeschichte betreibt, ein womöglich deutsch-italienischer monarchistischer Politiker, ein Schweizerischer Musikforscher (und -fälscher), ein französischer Flötenvirtuose und Nachfahre Jean-Pierre Bérangers, eine vermutlich irische Anhängerin keltischer Folklore. Der Palazzo der Marchesa gleicht äußerlich jenem venezianischen Gebäude, in dem Richard Wagner starb, in seinem Inneren sind gar ,,alle Stilepochen von der Gotik an vertreten“ (EW, 9), ein Cembalo gehörte einst Jean-Philippe Rameau, auch die konzertierende Flöte scheint von historischem Wert; Kleidung, Musik und die Säle, in denen sie aufgeführt wird, sind fein aufeinander abgestimmt.

"Hol dir deinen beneFIT" : Einführung eines Gesundheitspasses zur Förderung der Studierendengesundheit an der Universität Paderborn - Köster, Carolin; Schaper, Niclas; Fergland, Dennis; Bischof, Sandra; Kussin, Ulrich; Kämpfe, Astrid (Bewegungsorientierte Gesundheitsförderung an Hochschulen)

Körperlich-sportliche Aktivität und subjektiver Gesundheitszustand sowie studiumsspezifisches Stressempfinden bei Studierenden - Kämpfe, Astrid; Köster, Carolin; Brandl-Bredenbeck, Hans-Pater (Bewegungsorientierte Gesundheitsförderung an Hochschulen)

Exploring Tradeoffs between Specialized Kernels and a Reusable Overlay in a Stereo-Matching Case Study - Kenter, Tobias; Schmitz, Henning; Plessl, Christian (International Journal of Reconfigurable Computing (IJRC))
FPGAs are known to permit huge gains in performance and efficiency for suitable applications but still require reduced design efforts and shorter development cycles for wider adoption. In this work, we compare the resulting performance of two design concepts that in different ways promise such increased productivity. As common starting point, we employ a kernel-centric design approach, where computational hotspots in an application are identified and individually accelerated on FPGA. By means of a complex stereo matching application, we evaluate two fundamentally different design philosophies and approaches for implementing the required kernels on FPGAs. In the first implementation approach, we designed individually specialized data flow kernels in a spatial programming language for a Maxeler FPGA platform; in the alternative design approach, we target a vector coprocessor with large vector lengths, which is implemented as a form of programmable overlay on the application FPGAs of a Convey HC-1. We assess both approaches in terms of overall system performance, raw kernel performance, and performance relative to invested resources. After compensating for the effects of the underlying hardware platforms, the specialized dataflow kernels on the Maxeler platform are around 3x faster than kernels executing on the Convey vector coprocessor. In our concrete scenario, due to trade-offs between reconfiguration overheads and exposed parallelism, the advantage of specialized dataflow kernels is reduced to around 2.5x.

Easy-to-Use On-The-Fly Binary Program Acceleration on Many-Cores - Damschen, Marvin; Plessl, Christian (Proceedings of the 5th International Workshop on Adaptive Self-tuning Computing Systems (ADAPT))
This paper introduces Binary Acceleration At Runtime(BAAR), an easy-to-use on-the-fly binary acceleration mechanismwhich aims to tackle the problem of enabling existentsoftware to automatically utilize accelerators at runtime. BAARis based on the LLVM Compiler Infrastructure and has aclient-server architecture. The client runs the program to beaccelerated in an environment which allows program analysisand profiling. Program parts which are identified as suitable forthe available accelerator are exported and sent to the server.The server optimizes these program parts for the acceleratorand provides RPC execution for the client. The client transformsits program to utilize accelerated execution on the server foroffloaded program parts. We evaluate our work with a proofof-concept implementation of BAAR that uses an Intel XeonPhi 5110P as the acceleration target and performs automaticoffloading, parallelization and vectorization of suitable programparts. The practicality of BAAR for real-world examples is shownbased on a study of stencil codes. Our results show a speedup ofup to 4 without any developer-provided hints and 5.77 withhints over the same code compiled with the Intel Compiler atoptimization level O2 and running on an Intel Xeon E5-2670machine. Based on our insights gained during implementationand evaluation we outline future directions of research, e.g.,offloading more fine-granular program parts than functions, amore sophisticated communication mechanism or introducing onstack-replacement.

Improving Packet Processing Performance in the ATLAS FELIX Project – Analysis and Optimization of a Memory-Bounded Algorithm - Schumacher, Jörn; T. Anderson, J.; Borga, A.; Boterenbrood, H.; Chen, H.; Chen, K.; Drake, G.; Francis, D.; Gorini, B.; Lanni, F.; Lehmann-Miotto, Giovanna; Levinson, L.; et al. (Proc. Int. Conf. on Distributed Event-Based Systems (DEBS))

Aktuelles Schlagwort: Approximate Computing - Plessl, Christian; Platzner, Marco; Schreier, Peter J. (Informatik Spektrum)
Keywords: approximate computing; survey

Transparent offloading of computational hotspots from binary code to Xeon Phi - Damschen, Marvin; Riebler, Heinrich; Vaz, Gavin Francis; Plessl, Christian (Proceedings of the 2015 Conference on Design, Automation and Test in Europe (DATE))
In this paper, we study how binary applications can be transparently accelerated with novel heterogeneous computing resources without requiring any manual porting or developer-provided hints. Our work is based on Binary Acceleration At Runtime (BAAR), our previously introduced binary acceleration mechanism that uses the LLVM Compiler Infrastructure. BAAR is designed as a client-server architecture. The client runs the program to be accelerated in an environment, which allows program analysis and profiling and identifies and extracts suitable program parts to be offloaded. The server compiles and optimizes these offloaded program parts for the accelerator and offers access to these functions to the client with a remote procedure call (RPC) interface. Our previous work proved the feasibility of our approach, but also showed that communication time and overheads limit the granularity of functions that can be meaningfully offloaded. In this work, we motivate the importance of a lightweight, high-performance communication between server and client and present a communication mechanism based on the Message Passing Interface (MPI). We evaluate our approach by using an Intel Xeon Phi 5110P as the acceleration target and show that the communication overhead can be reduced from 40% to 10%, thus enabling even small hotspots to benefit from offloading to an accelerator.

FELIX: a High-Throughput Network Approach for Interfacing to Front End Electronics for ATLAS Upgrades - Anderson, J; Borga, A; Boterenbrood, H; Chen, H; Chen, K; Drake, G; Francis, D; Gorini, B; Lanni, F; Lehmann Miotto, G; Levinson, L; Narevicius, J; et al. (Journal of Physics: Conference Series)
The ATLAS experiment at CERN is planning full deployment of a new unified optical link technology for connecting detector front end electronics on the timescale of the LHC Run 4 (2025). It is estimated that roughly 8000 GBT (GigaBit Transceiver) links, with transfer rates up to 10.24 Gbps, will replace existing links used for readout, detector control and distribution of timing and trigger information. A new class of devices will be needed to interface many GBT links to the rest of the trigger, data-acquisition and detector control systems. In this paper FELIX (Front End LInk eXchange) is presented, a PC-based device to route data from and to multiple GBT links via a high-performance general purpose network capable of a total throughput up to O(20 Tbps). FELIX implies architectural changes to the ATLAS data acquisition system, such as the use of industry standard COTS components early in the DAQ chain. Additionally the design and implementation of a FELIX demonstration platform is presented and hardware and software aspects will be discussed.

Einleitung: Organisationen und Konventionen - Knoll, Lisa (Organisationen und Konventionen)

Organisationen und Konventionen. Die Soziologie der Konventionen in der Organisationsforschung

The Hidden Regulation of Carbon Markets - Knoll, Lisa (Historical Social Research)

MiLeNa – ein überregionales Programm zur MINT-Lehrernachwuchsförderung - Salinga, Christian; Heinke, Heidrun; Jonas-Ahrend, Gabriela; Theyßen, Heike; Bahr, Ursula; Erb, Roger

Einrichten - Bartz, Christina (Historisches Wörterbuch des Mediengebrauchs)

Bewertungsfernsehen - Bartz, Christina (Pop. Kultur & Kritik H. 7)

Kriegsausbruch, Kriegs Ausbruch, KriegsAusbruch: About the possible connection between linguistic variety and age, based on personal journals from 1892-1944 - Schuster, Britt-Marie (The lifespan perspective)
Keywords: Kommunikationsgeschichte

Wie geht’s (Dir)? Zur diachronen Entwicklung pragmatischer Phraseme im kontrastiven Vergleich - Schuster, Britt-Marie (Sektion A1. Beziehungsgestaltung durch Sprache. Akten des XIII. Internationalen Germanistenkongresses Shanghai 2015. Germanistik zwischen Tradition und Innovation (Publikationen der Internationalen Vereinigung für Germanistik (IVG)))
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Einfachheit, Wiederholung und Kontrast: Zur Konstanz sprachlicher Verfahren in der persuasiven Kommunikation - Schuster, Britt-Marie (Wirksame Rede im Frühneuhochdeutschen: Syntaktische und textstilistische Aspekte)
Keywords: Kommunikationsgeschichte

Wirksame Rede im Frühneuhochdeutschen: Syntaktische und textstilistische Aspekte - Schuster, Britt-Marie; Dogaru, Dana
Keywords: Kommunikationsgeschichte

Aligning training models with smartphone properties in WiFi fingerprinting based indoor localization - Hoang, Manh Kha; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (40th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2015))

„Unwälzbar ist der Stein ,es war': ewig müssen auch alle Strafen sein!" - Corall, Niklas (Nietzscheforschung)
Keywords: General Engineering

Heilige Wesen - Lebewesen - Corall, Niklas (Nietzscheforschung)
Keywords: General Engineering

Organizations, Climate Change, and Transparency - Hahn, Rüdiger; Reimsbach, Daniel; Schiemann, Frank (Organization & Environment)
The debate surrounding climate change often centers on companies’ contributions to global warming, which has led to an increase in the importance of carbon disclosure. We evaluate the current state of related research and identify its trends, coherences, and caveats via a systematic literature review. Sociopolitical theories of disclosure, economic theories of disclosure, and institutional theory serve as the main theoretical anchors for our exploration. The existing research emphasizes the determinants and, to a lesser extent, effects of carbon disclosure, as well as the associated regulatory issues such as voluntary versus mandatory disclosure. Additionally, we discuss related topics, such as assurance and risks. We find that a large portion of scholarly work provides no link to theory, despite the fact that such links can be identified, for example, from the financial disclosure literature. Finally, we report on the established knowledge and examine the need for additional research.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science